Factors Related To Food Waste in Patients with Diabetes Mellitus at Imanuel Hospital Lampung - Nathasa Khalida Dalimunthe; Tantri Adhayani Pratiwi; Edwin edwin; Rusiati Rusiati (Darussalam Nutrition Journal, 2023)
Background: According to the survey, the percentage of food waste’s diabetes melitus patients in the Imanuel Hospital of Bandar lampung was 38% and still have not reached the minimum service standars (<20%). Objective: This study aimsed to analyze the factors associated with food waste in diabetes melitus patients in Hospital Imanuel. Methods: Descriptive analytic research using cross sectional study design. The study used 50 samples was take with purposive sampling. The age, sex, food appearance, taste of food and service providers data were obtained by questionnaires, and food waste data were obtained by comstock form. The data analysis used was descriptive and inferential using the Chi Square statistical test. Results: About 46% of patients was 56-65 years old, and 78% was sex women. Leftovers from patients in the good category were 15 respondents (30%) while those who had leftovers that were not good were 35 respondents (70%). There was significant association between  appearance of food (p-value=0,005)  and taste of food (p-value=0,002) with the food waste. There was no significant association  between service providers (p-value=0,776) with the food waste. Conclusion: Factors related to leftovers from diabetes mellitus patients at Immanuel Hospital are the appearance and taste of the food . Therefore, these two variables need to be considered in order to minimize food waste in diabetes mellitus patients at Immanuel Hospital.